Pengembangan Kemampuan Berhitung Permulaan Anak Usia Dini melalui Permainan Edukatif Berbasis Matematika - Anggriani Amir; Abdul Majid; Fauziah Kamaruddin (ALSYS, 2026)
Although the development of early childhood numeracy skills has received considerable attention in previous studies, research that specifically discusses the development of early counting skills through mathematics-based educational games at PAUD Raodatul Jannah Baru-Baru Tanga remains limited. This study aimed to analyze the development of early childhood counting skills through mathematics-based educational games. This study used a qualitative approach with a case study design. The research subjects were Group B early childhood students at PAUD Raodatul Jannah Baru-Baru Tanga, with the teacher serving as the main informant. Data were collected through observation, interviews, and documentation, and were then analyzed through the stages of data reduction, data presentation, and conclusion drawing. The results showed that mathematics-based educational games, such as number cards, counting blocks, and games involving matching the number of objects, helped improve children’s ability to recognize numbers, count objects, and understand simple addition concepts. The learning process also became more engaging, interactive, and enjoyable, thereby increasing children’s motivation and active participation in learning activities. In addition, teachers played an important role in creating game-based learning that was directed and meaningful. These findings contribute to the development of play-based early childhood mathematics learning and broaden understanding of numeracy strengthening in the context of early childhood education. The conclusion of this study confirms that mathematics-based educational games can serve as an effective and child-centered learning strategy for improving early counting skills in early childhood education.